Estudos de produção de biogás em suinocultura ciclo completo usando um biodigestor de lagoa coberta circular com agitação, aquecimento e isolamento térmico - Soares, Clenoir Antonio (2024)
The research was carried out to investigate biogas production on a full-cycle pig farm with accommodation for 3,500 sows in a Piglet Production Unit (PLU) system and 10,000 animals in the finishing cycle. With the expansion of the herd after 2016, in order to meet the current volume of effluent of 165 m³/day, the biodigestion unit needed to be restructured with other technologies, and a circular covered lagoon biodigester equipped with an agitation system, heating, thermal insulation and a hydraulic retention time of 26 days was also implemented in the system. The study and investments were therefore necessary to prevent the three existing piston flow digesters from collapsing due to silting from the different loads. In this way, the organic loads from the buildings followed a weekly management schedule and were directed to the new biodigester, with their different characteristics in terms of physical-chemical composition and hydraulic retention time in the buildings. With the anaerobic processing of the organic loads in the new biodigester, it was possible to obtain a biogas production of 635.62 m3N.d-1 and an average efficiency of 61.32% for removing the COD load. An added volatile solids yield of 0.193 m3 of biogas per kg VS per m3 of reactor was also observed, as well as an added COD yield of 0.086 m3 of biogas per kg COD per m3 of reactor, with an average pH value of 7.53 and a heat transfer rate of up to 7°C. The quantification of biogas production made it possible to find out about the operation of off-grid electricity generation, which amounted to 20.31%, and to evaluate the cogeneration of hot water used in the biodigester's internal heating system. The investment was amortized in 5 years and 5 months, with an IRR of 4.03%, NPV of R$ 99,806.96 and 0% TMA.